Beyond The Brew: Crafting Kopi Kenangan Purchase Decisions Through Store Atmosphere, Promotions, And Service Quality - Fatkar, Budiastuti; Zasafani, Deny; Atrisia, Marchela Indah; Astuti, Sherly (Media Bisnis, 2024)
The culinary business competition holds significant popularity among Indonesian individuals, particularly within the food and beverage industry. Coffee shops have been undergoing significant expansion and can now be found in numerous locations. One notable example of this growth is Kopi Kenangan, which has emerged as one of the largest coffee shop chains. The primary objective of this study is to examine the impact of store atmosphere, promotions, and service quality on consumer purchasing behaviour at the Curug branch of Kopi Kenangan in Tangerang City. The target group for this study comprises individuals who have engaged in transactions at the Curug Tangerang Branch of Kopi Kenangan between December 2022 and June 2023. This study employed a non-probability sampling approach, specifically utilising the incidental sampling technique. The overall sample size consisted of 125 respondents. This study employs the technique of multiple linear regression analysis, utilising the statistical software SPSS 26 for Windows. The findings of the study indicate that factors such as store atmosphere, promotions, and service quality have a partial and simultaneous impact on consumer purchase decisions. For those involved in the coffee industry, this study's managerial implications may be useful.